OP0036 Fewer Patients on Biologicals and Better Functional Ability Two Years after Induction Therapy with Combination DMARD Therapy versus Methotrexate Monotherapy. (10th June 2014) - Kuijper, M.; Weel, A.; de Jong, P.; Gerards, A.; van Zeben, J.; Tchetverikov, I.; de Sonnaville, P.; van Krugten, M.; Grillet, B.; Hazes, M.; Luime, J.
Abstract : Background: Fewer patients on biologicals and better functional ability two years after induction therapy with combination DMARD therapy versus methotrexate monotherapy Objectives: To assess differences in frequency of biological therapy use in early RA patients two years after starting induction therapy according to three different treatment regimens Methods: Data were used from patients with recent-onset arthritis participating in a single-blinded clinical trial (Treatment in the Rotterdam Early Arthritis CoHort (tREACH)) [1, 2] in which three induction therapy strategies were compared: (A) combination therapy (methotrexate (MTX) + sulfasalazine + hydroxychloroquine) with glucocorticoids (GCs) intramuscularly; (B) combination therapy with an oral GC tapering scheme and (C) MTX with oral GCs similar to B. Disease activity scores (original DAS) were assessed every 3 months. Functional ability was assessed using the Health assessment questionnaire (HAQ). Actual medication use was obtained from medical charts and from patient diaries. Data were analysed using simple descriptive statistical techniques. Results: 281 patients (91 men, 190 women; mean baseline DAS 3.4, median baseline HAQ 0.75) were initially randomized. Data on medication use at 2 years were available from 166 patients (59%). Mean DAS was 1.72 (95%CI 1.59-1.86) at 24 months with similar results for the initial treatment groups A-C. DAS remission (DAS<1.6) was achieved by 50% of patients. Median HAQ (min-max) was 0.38 (0-2) for all patients but varied in the treatment groups: A. 0.13 (0-1.6), B. 0.44 (0-2) and C. 0.63 (0-2). HAQ was significantly higher in group C versus A (p=0.042), while no significant difference was observed for group A versus B (p=0.39). Conventional DMARDs only were used in 58% of patients (A. 60%, B. 75% and C. 43%). Biological DMARDs only were used in 5% of patients (A. 8%, B. 2% and C 7.%). Thirteen percent of patients did not use any DMARD at all (A. 14%, B. 9% and C. 16%). Patients in group C used biological DMARDs more often compared to B (p=0.004), but no statistical difference was observed between groups A and B (p=0.241). Conclusions: We observed lower use of biological therapy and better functional ability in induction triple therapy compared to induction monotherapy MTX with GC bridging at 2 years of follow-up in the treat-to-target tREACH study. No differences were found for disease activity scores. References: Claessen et al. Use of risk stratification to target therapies in patients with recent onset arthritis; design of a prospective randomized multicenter controlled trial. BMC Musculoskelet Disord 2009;10:71. De Jong et al. Induction therapy with a combination of DMARDs is better than methotrexate monotherapy: first results of the tREACH trial. Ann Rheum Dis. 2013 Jan;72(1):72-8. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5357